2021
DOI: 10.1111/mpp.13040
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the transcriptomic, metabolomic, and gene regulatory responses to Puccinia sorghi in maize

Abstract: Common rust, caused by Puccinia sorghi, is a widespread and destructive disease of maize. The Rp1‐D gene confers resistance to the P. sorghi IN2 isolate, mediating a hypersensitive cell death response (HR). To identify differentially expressed genes (DEGs) and metabolites associated with the compatible (susceptible) interaction and with Rp1‐D‐mediated resistance in maize, we performed transcriptomics and targeted metabolome analyses of P. sorghi IN2‐infected leaves from the near‐isogenic lines H95 and H95:Rp1‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 91 publications
1
19
0
Order By: Relevance
“…The homologs of these genes in different plant species also act in plant immunity (Coll et al, 2010;Senthil-Kumar et al, 2010;Gallego-Giraldo et al, 2011;Zeilmaker et al, 2015), suggesting the functional association between disease resistance and HR regulation. Recently, it was reported that the transcriptional responses triggered by Rp1-D21 are broadly similar to those triggered by its wild type (WT) counterpart Rp1-D, which is activated by Puccinia sorghi infection (Kim et al, 2021). The DEGs identified in Rp1-D21 are highly correlated with disease resistance; therefore, Rp1-D21 can be used as a quick and effective tool for exploring new HR regulation and disease resistance genes.…”
Section: The Autoactive Rp1-d21 Mt Is An Excellent Tool For the Identification Of Disease Resistance Genes In Maizementioning
confidence: 99%
“…The homologs of these genes in different plant species also act in plant immunity (Coll et al, 2010;Senthil-Kumar et al, 2010;Gallego-Giraldo et al, 2011;Zeilmaker et al, 2015), suggesting the functional association between disease resistance and HR regulation. Recently, it was reported that the transcriptional responses triggered by Rp1-D21 are broadly similar to those triggered by its wild type (WT) counterpart Rp1-D, which is activated by Puccinia sorghi infection (Kim et al, 2021). The DEGs identified in Rp1-D21 are highly correlated with disease resistance; therefore, Rp1-D21 can be used as a quick and effective tool for exploring new HR regulation and disease resistance genes.…”
Section: The Autoactive Rp1-d21 Mt Is An Excellent Tool For the Identification Of Disease Resistance Genes In Maizementioning
confidence: 99%
“…In Arabidopsis, the exaggerated HR induced in AtMYB30-overexpressing lines was suppressed by the loss of function of the acyl-ACP thioesterase FATB, which causes severe defects in the supply of fatty acids for VLCFA biosynthesis (Raffaele et al, 2008). In our study of the maize transcriptional response to P. sorghi, several VLCFA biosynthetic genes differentially accumulated in near-isogenic lines differing for induction of the defence response mediated by Rp1-D (Kim et al, 2021). We found that the transcript levels of four VLCFA biosynthetic genes that carried AtMYB30-specific binding sites in their promoters were down-regulated in plants in which ZmMYB83 expression was suppressed and up-regulated in plants in which ZmMIEL1 expression was suppressed (Figure 8a), as would be expected if ZmMIEL1/ZmMYB30 acts in a similar fashion to AtMIEL1/ AtMYB30.…”
Section: Discussionmentioning
confidence: 72%
“…Within these two groups the sequences were almost identical. Interrogating data from a separate RNA-Seq study (Kim et al, 2021), we noted that expression of ZmMIEL1 during the Rp1-D-mediated ETI response to P. sorghi was not induced significantly until the 120-hr postinoculation (hpi) timepoint. In contrast in a nearisogenic susceptible line without Rp1-D, ZmMIEL1 was induced early in the maize-P. sorghi interaction at 12 hpi but was induced less at 24 hpi and not at all at 120 hpi (Figure S6).…”
Section: Grmzm2g056270 Encodes An Arabidopsis Miel1 Homologmentioning
confidence: 90%
“…Besides, metabolomic profiling of soybean leaf tissues by GC-MS and LC-MS analyses revealed the role of phytochemical metabolism, as well as sugar and nitrogen metabolism in conferring tolerance to combined drought and heat stress conditions ( Das et al, 2017 ). Integrated metabolomic, transcriptomic and gene regulatory network analyses of common rust ( Puccinia sorghi ) resistance in maize identified a number of Rp1-D -mediated defense response metabolites (including chlorogenic acid, caffeic acid, ferulic acid, flavonoids, terpenoids, kauralexins and zealexins) and genes involved in SA biosynthesis (especially, calmodulin-binding protein 60G and systemic acquired resistance deficient 1, SARD 1; and several TFs such as WRKY53, BZIP84, NKD1, BHLH124 and MYB100) as potentially critical regulators of P. sorghi resistance in maize ( Kim S.B. et al, 2021 ).…”
Section: Omics Facilitated Crop Improvement For Abiotic and Biotic Stress Resistancesmentioning
confidence: 99%